Uneven Odds, Unequal Outcomes : Inequality of Opportunity in the Middle East and North Africa - Krishnan, Nandini (Washington, DC: World Bank, 2016)
Perceptions of eroding living standards and low life satisfaction are widespread in the Middle East and North Africa region today, along with pessimism about prospects for economic mobility. Conventional measures of economic well-being offer little in the way of explanation – in most countries in the region, extreme poverty is low and declining and economic inequality is lower than in other parts of the world. This book investigates possible reasons for this disconnect, focusing on the role played by inadequate and unequal access to opportunities to realize one’s aspirations for economic mobility. The inability of most countries in the region to meet the aspirations of citizens is closely linked to persistent weaknesses in the labor markets where the pace of job creation has been chronically below levels required to absorb the growing and increasingly better educated population. A high degree of segmentation in the labor markets also puts the youth and women in the region at a particular disadvantage.